2012
DOI: 10.1088/0952-4746/32/3/261
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal aberrations in peripheral blood lymphocytes exposed to a mixed beam of low energy neutrons and gamma radiation

Abstract: Cells exposed to thermal neutrons are simultaneously damaged by radiations with high and low linear energy transfer (LET). A question relevant for the assessment of risk of exposure to a mixed beam is whether the biological effect of both radiation types is additive or synergistic. The aim of the present investigation was to calculate whether the high and low LET components of a thermal neutron field interact when damaging cells. Human peripheral blood lymphocytes were exposed to neutrons from the HB11 beam a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Experimental systems using fission neutrons are usually a mixture of differing levels of γ-rays. Yet, at least at biologically relevant moderate doses, nil or negligible levels of interaction of high– and low–linear energy transfer (LET) radiations have been reported for various biological endpoints in mixed radiation fields [3441]; however, others have reported synergistic-like effects [42, 43]. …”
Section: Data Assessment and Results Of Analysesmentioning
confidence: 99%
“…Experimental systems using fission neutrons are usually a mixture of differing levels of γ-rays. Yet, at least at biologically relevant moderate doses, nil or negligible levels of interaction of high– and low–linear energy transfer (LET) radiations have been reported for various biological endpoints in mixed radiation fields [3441]; however, others have reported synergistic-like effects [42, 43]. …”
Section: Data Assessment and Results Of Analysesmentioning
confidence: 99%
“…In addition to the differences between high-LET and low-LET radiation, there are conflicting results on whether irradiation of cells with low-LET radiation before high-LET radiation, as would occur in a space environment, has a synergistic or protective effect on DNA damage. Most researchers have stated there is a detrimental effect of pre-irradiation with low-LET radiation followed by high-LET radiation, with peak chromosomal damage at a 30-min interval between the irradiation regimes [ 68 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. However, Buonanno et al [ 87 , 88 ] and Stoilov et al [ 87 , 88 ] have observed a protective effect if the interval is up to 24 h, with researchers attributing this effect to the upregulation of redox scavengers of antioxidants.…”
Section: General Effects Of Radiation On Dna/cancer Cellsmentioning
confidence: 99%
“…Evaluations of the dicentric chromosome assay (DCA) RBE M of low-energy thermal neutrons in human peripheral blood lymphocytes are reported in several previous publications (Table 1), with maximum RBE (RBE M ) results ranging from 10.8 ± 1.8 to 51.1 ± 31.3 [16][17][18][19]. The wide range of DCA RBE values and the large associated errors makes pinpointing a single thermal neutron RBE value difficult.…”
Section: Introductionmentioning
confidence: 99%